2021
DOI: 10.1037/cdp0000343
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms in Chinese immigrant mothers: Relations with perceptions of social status and interpersonal support.

Abstract: Objectives: The present study examined how English proficiency, aspects of social status (education, income, and shifts in subjective social status), and interpersonal support were directly and indirectly associated with variations in depressive symptoms among Chinese immigrant mothers. Method: Individual semistructured interviews and questionnaires were administered to 257 first-generation Chinese immigrant mothers in the United States (Mage = 37.87 years). Participants reported on their English proficiency, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 78 publications
(120 reference statements)
1
6
0
Order By: Relevance
“…Our results support previous findings of an association between SES indicators and health-related issues and showed that SSS influence health needs reporting and health-seeking behaviour above and beyond traditional SES indicators [65][66][67].…”
Section: Discussionsupporting
confidence: 92%
“…Our results support previous findings of an association between SES indicators and health-related issues and showed that SSS influence health needs reporting and health-seeking behaviour above and beyond traditional SES indicators [65][66][67].…”
Section: Discussionsupporting
confidence: 92%
“…Four of the papers reviewed [63][64][65][66] did not find any significant association between LP and mental disorders. No significant relationships between LP and depressive symptoms severity were found among elderly Korean immigrants living in Canada [63] or female Asian immigrants residing in Korea after an international marriage [64].…”
Section: No Relationship Between Lp and Mental Disordersmentioning
confidence: 87%
“…No significant relationships between LP and depressive symptoms severity were found among elderly Korean immigrants living in Canada [63] or female Asian immigrants residing in Korea after an international marriage [64]. No direct relationship was found between LP and depressive symptoms in Chinese mothers living with their children in the United States, even though LP was found to exert an indirect effect (mediated by economic and social factors) on depressive symptoms [66]. One other study did not find any significant relationships between LP and the prevalence of PTSD and grief-related symptoms [65].…”
Section: No Relationship Between Lp and Mental Disordersmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, while the associations between higher family SES and better executive function in children have been consistently demonstrated across sociocultural groups Obradovi c & Willoughby, 2019), investigations of family SES and selfregulation among immigrant families from any Asian American ethnic group are limited and indicate mixed or nonsignificant associations between family SES, EF, and other indicators of children's self-regulation, such as effortful control and behavioral regulation (Chen, Zhou, Main, & Lee, 2015 ;Chen et al, 2015;Liew, Kwok, Chang, Chang, & Yeh, 2014;Williams, Uchikoshi, Bunge, & Zhou, 2019). Furthermore, while family SES is commonly operationalized as a composite variable of household income and education, previous studies with Chinese immigrant families indicate that income and education level are dissociable aspects of social status that have distinct associations with socioemotional processes (Chen, Zhang, Liu, & Wang, 2020;Chen & Zhou, 2019).…”
Section: Ses Acculturation and Self-regulationmentioning
confidence: 98%